Krisekommunikation i kommunerne - Herping, Søren Stentoft (Politik, 2011)
In recent years, the academic literature on crisis communication has increased. The literature is however driven forward by studies in the private sector. In a public sector context attention has mostly been given to the political scandal or what could be labeled emergency communication primarily focused on natural or man made disasters. The municipalities in Denmark are however in a strong need for knowledge regarding crisis communication. Some have already been the center of a crisis, while others are preparing themselves to be the center of a crisis. Everybody knows that crisis will come, but nobody knows when. This paper will draw on a crisis in a municipality that has already had the “global” media attention in Denmark, the so called Brønderslevsag. The aim of the paper is twofold. First, to build a theory regarding crisis commu- nication, and second to make a tentative test of the theory in an empirical case. To this end, a qualitative study is conducted in a single case with a deductive research design. The theoretical point of departure is a combination of literature on crisis communication and decision making in public administration. Through this theoretical mix the ambition is that crisis communication studies can enter the specific context of public administration. The analysis shows that the preparedness of a possible crisis is crucial to the municipality, and that the municipality has a tendency to get involved in a blame game that does not fit the discourses in the public arena. Therefore the municipality appears to center around themselves, even though they try to be very open to the public.